ОСОБЛИВОСТІ РОЗРАХУНКУ НАПІВПРОВІДНИКОВИХ ПЕРЕТВОРЮВАЧІВ ПОСТІЙНОЇ НАПРУГИ НА ОСНОВІ УСЕРЕДНЕННЯ В ПРОСТОРІ СТАНІВ - Руденко, Ю.В. (Інститут електродинаміки Національної академії наук України, 2020)
The application of state space averaging method using Lagrange theorems for calculating of semiconductor converters in a formalized matrix form is considered. Analytical expressions are obtained for calculating the average and pulsating components of variable states in two-interval processes in single-cycle converters. The matrix coefficients of model with averaged variables for buck converter in the continuous-current choke mode are determined for illustration. Advantages of considered method using Lagrange theorems are shown, which are characterized by at least of six times less computational complexity in comparison with traditional methods based on solving of differential equations (fitting method) and the possibility of pulsating components calculation in comparison with classical averaging methods. References 12, figures 2, tables 2.